2016
DOI: 10.7860/jcdr/2016/17482.7200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anthropometric Indices, Salt Intake and Physical Activity in the Aetiology of Prehypertension

Abstract: Exercise capacity was found decreased in pre-hypertensives and they have high daily salt intake. Also, weight and age emerged as independent risk factors for SBP and DBP respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Moinuddin et al . 11 showed that daily salt intake of prehypertensives (21.2 ± 1.2 g/day) was significantly greater than normotensive subjects (9.0 ± 0.5 g/day). This result is similar to our study, which found that compared with participants without prehypertension, those with prehypertension tended to have higher urinary sodium excretions (5.20 ± 1.38 vs .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moinuddin et al . 11 showed that daily salt intake of prehypertensives (21.2 ± 1.2 g/day) was significantly greater than normotensive subjects (9.0 ± 0.5 g/day). This result is similar to our study, which found that compared with participants without prehypertension, those with prehypertension tended to have higher urinary sodium excretions (5.20 ± 1.38 vs .…”
Section: Discussionmentioning
confidence: 93%
“…Several mechanisms, including endothelial dysfunction, oxidative stress, inflammation, insulin resistance, and neurogenically mediated increase in peripheral resistance, contribute to the harmful effects of dietary salt 9 , 10 . Recent studies have shown that increased salt intake may be associated with the pathogenesis of prehypertension 11 13 . However, data on the association between dietary salt intake and prehypertension are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Evidence suggests that obesity is related to prehypertension etiology, a state of excess adipose tissue in the body. 10,11 Obesity's prevalence in people aged 18 years old and above in Indonesia has increased by 11.3% in one decade (2007-2018). 2 The increase could lead to a higher presence of prehypertension, hypertension, and increased cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Although few studies from India have attempted to estimate the impact of prehypertension, those studies were limited in application because of their focus on opportunistic screening in facility-based and industrial settings, thereof the majority participatory population being young adult males. [ 13 14 15 16 17 18 19 ] Moreover, previous studies have reported the variations based on demographic characteristics and studies which looked into the role of behavioral and lifestyle factors in prehypertension are scarce.…”
Section: Introductionmentioning
confidence: 99%